Lisbon Story, from the Pombaline Architect to Siza - Couceiro, Joana (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2020)
The term ‘Façadism’ has acquired a negative connotation, but the History of Architecture shows that it has not always been like this. As an architectural feature with a certain autonomy, the façade allows for a formal discord between the exterior and the interior of buildings (floors and storeys), reconciles the scale of the city with the human scale, catalyses the design of the public space and the space of intimacy, stimulates harmony between the urban and domestic environments, and makes it possible to breathe natural air and condition the air inside the building.